2023
DOI: 10.3390/ph16070957
|View full text |Cite
|
Sign up to set email alerts
|

Pectin Nanoparticle-Loaded Soft Coral Nephthea sp. Extract as In Situ Gel Enhances Chronic Wound Healing: In Vitro, In Vivo, and In Silico Studies

Abstract: This study shed light for the first time on the in vivo diabetic wound healing potential activity of natural marine soft coral polymeric nanoparticle in situ gel using an excision wound model. A Nephthea sp. methanol–methylene chloride extract loaded with pectin nanoparticles (LPNs) was created. For the preparation of in situ gel, ion-gelation techniques, the entrapment efficiency, the particle size, the polydispersity index, the zeta potential, the in-vitro drug release, and a transmission electron microscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…[194] Hassan et al aimed to develop a formulation based on the extract of a soft coral, Nephthea sp., for the treatment of chronic wounds; they assessed the inhibitory effect of the extract on MMP-1 and reported an IC 50 value of 0.26 μg mL −1 . [196] Chin et al assessed the influence of doxycycline and tetracycline on the proteolytic activity of exudates obtained from chronic wounds by using azocollagen (azocoll) as the substrate. [94] They found that both of them dose-dependently reduced the proteolytic activity, which was ≈90% and 60% for doxycycline and tetracycline, respectively, at a 5 mM concentration.…”
Section: Influence Of Different Agents On Proteases In Solutions and ...mentioning
confidence: 99%
“…[194] Hassan et al aimed to develop a formulation based on the extract of a soft coral, Nephthea sp., for the treatment of chronic wounds; they assessed the inhibitory effect of the extract on MMP-1 and reported an IC 50 value of 0.26 μg mL −1 . [196] Chin et al assessed the influence of doxycycline and tetracycline on the proteolytic activity of exudates obtained from chronic wounds by using azocollagen (azocoll) as the substrate. [94] They found that both of them dose-dependently reduced the proteolytic activity, which was ≈90% and 60% for doxycycline and tetracycline, respectively, at a 5 mM concentration.…”
Section: Influence Of Different Agents On Proteases In Solutions and ...mentioning
confidence: 99%
“…The alcyonarian Litophyton viridis was observed to provide chemical protection for the fish Abudefduf leucogaster [18]. In addition to the ecological role, the extracts of several soft corals of the genus Litophyton have been biologically screened and showed a variety of potent bioactivities, such as antioxidant [19], genotoxic [20], cytotoxic [19,21,22], HIV-1 enzyme inhibitory [21], antibacterial [22], anti-inflammatory [23], antifungal [24], and wound healing [25] activities. Chemical investigations on Litophyton soft corals were carried out by researchers worldwide and revealed that soft corals of the genus Litophyton are prolific producers of bioactive secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%